Algorithm for Diagnosis of Patients with Ischemic Heart Disease Depending on the Presence of Significant Coronary Artery Lesions - Marushko, Yevhen Yu.; Rudenko, Nadiya M.; Dzhun, Yana Yu. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the structure of ischemic heart disease and the prevalence of myocardial ischemia with no ob-structive coronary arteries among patients who underwent elective coronary angiography. Materials and methods. We examined 1,200 patients with a clinical diagnosis of ischemic heart disease. After coro-nary angiography all the patients with non-stenotic coronary arteries underwent hyperventilation challenge test to ex-clude vasospastic angina and echocardiographic study with intravenous administration of dipyridamole to assess the index of coronary reserve and longitudinal strain. Results. The mean age of the study participants was 59.1 ± 4.2 years. The number of male and female subjects was comparable, amounting to 493 (48.8%) and 517 (51.2%), respectively. Stenotic coronary arteries were detected in 699 patients (74.1%). The number of women without hemodynamically significant lesions was twice as large than that of men (210 [67.5%] vs. 101 [32.5%]). Among the examined patients with non-stenotic atherosclerosis of the coronary arteries, 241 patients (77.4%) were diagnosed with coronary microvascular dysfunction, 19 (6.1%) with vasospasm of the coronary arteries, and 2 patients (0.6%) were diagnosed with a combination of vasospastic and microvascular angina. In 36 (73.5%) of 49 patients, a segmental decrease in longitudinal strain of the apex/individual apical segments of the left ventricle was found. In patients without obvious micro- and macrovascular pathology, the interventricular septum was significant enlarged. In 9 (18.4%) of 49 patients, a diagnosis of hypertrophic cardiomyopathy was established. Conclusion. Patients with ischemia with no obstructive coronary arteries require careful examination and compari-son of clinical signs with the results of objective tests. Understanding the prevalence and mechanisms of the problem is a key to improving the diagnosis and treatment of cardiovascular complications in this group.